Mapas mentais e o ensino de geografia na EJA: desafios para as leituras cotidianas e sua relação com os conteúdos escolares - Lopes, Marcos Piter (2015)
This research aims to investigate the contribution of the use of mind maps in teaching Geography in 9th grade of Youth and Adult Education (EJA) in a public school in the city of Inhumas / GO, from the integration of geographic and cartographic knowledge present in that language and that allows students to make a critical reading of the world, tied their realities and daily practices. For the purposes proposals were met, it was necessary to recognize and understand the importance of mental maps in teaching geography at EJA, from the development of school activities, and to examine the potential that the mental map presented as relevant language for the student develop world readings, linking scientific knowledge with everyday. It will also be important to highlight the social Cartography in the teaching of Geography, highlighting the school teaching-learning process and verify the associations of geographical concepts in the production of mental map, from the relationship with the studied school subjects. This research works with research in the case study approach. Thus, the survey and analysis of bibliographic references of Geography and Cartography School, as well as conducting observations and application of mind maps proposals to know the real situation experienced by teachers and students in the classroom was essential, as regards the contribution that can provide maps for teaching geography, linking content with social practices. The main results of research on the link between the maps and your school use were highlighted; maps as a means of appropriation and daily representation; and care that students must observe when integrating the Cartography and the teaching of geography. Thus, the appreciation of everyday life, as the place of decisions and experiences that make individuals, it is important in this approach to geographic and cartographic education in an attempt to observe the importance of private life relationships with scientific knowledge to build a critical thinking about the world. Thus the construction of mental maps becomes pedagogical practice instrument in Geography for individuals to recognize the geographic content in the daily life of the same.